Characterisation of a vascular self-healing cementitious material system: Flow and curing properties. (10th June 2020) - Selvarajoo, T.; Davies, R.E.; Gardner, D.R.; Freeman, B.L.; Jefferson, A.D.
Highlights: New flow and curing data for healing agents in a cementitious vascular system. New insights into the nature of cyanoacrylate curing fronts in concrete cracks. Characterisation of the sorption behaviour of cyanoacrylate in concrete. Characterisation of cyanoacrylate flow within discrete concrete cracks. Constitutive equations and parameters for cyanoacrylate flow and curing n concrete. Abstract: A series of characterisation studies are reported that provide new data on the behaviour of a self-healing cementitious material (SHCM) system. A 'model' material system is selected for study that comprises cyanoacrylate (CA) filled channels in concrete structural elements. The focus of the work is on transport and curing properties of the healing-agent, with the results of four separate studies being presented. The experimental programme encompasses the capillary flow behaviour of CA in a static natural crack, the sorption of healing-agent through a cracked surface into a concrete specimen, the development and progress of a CA curing front adjacent to a concrete substrate and the dynamic flow characteristics of CA in capillary channels. A theoretical relationship is established for each of these processes, which allows meaningful parameters to be determined that help characterise the behaviour of the material system. In all cases, the processes were shown to have a significant degree of variability but, equally, to exhibit strong behavioural trends.